2001
DOI: 10.1128/mcb.21.14.4818-4828.2001
|View full text |Cite
|
Sign up to set email alerts
|

The Cell Cycle-Regulatory CDC25A Phosphatase Inhibits Apoptosis Signal-Regulating Kinase 1

Abstract: CDC25A phosphatase promotes cell cycle progression by activating G 1 cyclin-dependent kinases and has been postulated to be an oncogene because of its ability to cooperate with RAS to transform rodent fibroblasts. In this study, we have identified apoptosis signal-regulating kinase 1 (ASK1) as a CDC25A-interacting protein by yeast two-hybrid screening. ASK1 activates the p38 mitogen-activated protein kinase (MAPK) and c-Jun NH 2 -terminal protein kinase-stress-activated protein kinase (JNK/SAPK) pathways upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 68 publications
1
67
0
Order By: Relevance
“…18 Another report demonstrated that Cdc25A inhibited cytoplasmic ASK1 independent of its phosphatase activity, thereby blocking cell death triggered by oxidative stress. 19 Hence, we fused the cDNA of Cdc25A to that of ER, which allows for Tamoxifen (4-OHT)-mediated shuttle of the Cdc25A:ER protein from the cytoplasm into the nucleus. The results from this investigation suggested that Cdc25A protected from apoptosis only when it was localised in the cytoplasm, because upon 4-OHT treatment, the cytoplasmic Cdc25A:ER level diminished and increased in the nuclei of rat 423 cells within 2 h, followed by degradation within 8 h. Hence, the loss of antiapoptotic function of Cdc25A:ER correlated with the decreased cytoplasmic expression upon exposure to 4-OHT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Another report demonstrated that Cdc25A inhibited cytoplasmic ASK1 independent of its phosphatase activity, thereby blocking cell death triggered by oxidative stress. 19 Hence, we fused the cDNA of Cdc25A to that of ER, which allows for Tamoxifen (4-OHT)-mediated shuttle of the Cdc25A:ER protein from the cytoplasm into the nucleus. The results from this investigation suggested that Cdc25A protected from apoptosis only when it was localised in the cytoplasm, because upon 4-OHT treatment, the cytoplasmic Cdc25A:ER level diminished and increased in the nuclei of rat 423 cells within 2 h, followed by degradation within 8 h. Hence, the loss of antiapoptotic function of Cdc25A:ER correlated with the decreased cytoplasmic expression upon exposure to 4-OHT.…”
Section: Discussionmentioning
confidence: 99%
“…However, Cdc25A also interacts with Raf1 by virtue of 14.3.3 proteins [16][17][18] and apoptosis signalregulating kinase (ASK)1. 19 This, in contrast, points to a cytoplasmic function of Cdc25A. It was demonstrated recently that in rat 423 cells the bulk of Cdc25A was actually localised in the cytoplasm and that apoptosis was inhibited by Cdc25A due to the PKB-protein kinase B (Akt) survival pathway activation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Cdc25A, which is involved in the control of the G 1 /S transition, binds to a region adjacent to the ASK1 kinase domain and inhibits the kinase activity of ASK1 in a manner independent of the phosphatase activity. 47 As Cdc25A and Cdc25C proteins function in different stages of the cell cycle, 2,3,5 ASK1 might be regulated in several stages of the cell cycle. There are several pieces of evidence that ASK1 phosphorylation is cell cycle dependent.…”
Section: Discussionmentioning
confidence: 99%
“…However, oxidative stress causes dissociation of the Trx-ASK1 complex leading to activation of JNK and p38. CDC25A, a phosphatase that promotes cell cycle progression also binds to and inhibits ASK1 activity, and when overexpressed, CDC25A can suppress activation of p38 and JNK1 and reduce cell death triggered specifically by oxidative stress (Zou et al, 2001). Whether other MAPKKK are also subject to such redox regulation is not clear, but a similar mechanism might function at the level of JNK to influence its activity.…”
Section: Sapk Pathwaysmentioning
confidence: 99%